SAT0192 Relationship between clinically detected joint swelling and effusion diagnosed by ultrasonogrpahy in talocrural joints in patients with rheumatoid arthritis. (1st June 2001) - Luukkainen, RK; Huhtala, H; KoskiHuhtala, JM
Abstract : Background: In clinical investigation it is often difficult to know if there is effusion in talocrural (TC) joint or not. Objectives: To compare the relationship between clinically detected swelling and effusion diagnosed by ultrasonography (US) in TC joints in patients with rheumatoid arthritis (RA). Methods: Thirty-one consecutive patients with RA entered the study. Twenty healthy persons formed a control group. In clinical assessment the TC joint was evaluated on the scale: normal or swelling. The US of the same joints was carried out. Altogether 62 TC joints of the RA patients and 40 of those of the controls were studied. All the clinical assessments were performed by one doctor and the US investigations by another and they were blinded of one others results. Results: Normal upper limit of the measurement between the talus and the joint capsule was evaluated from the control group. It was 3.1 mm (mean + 2 SD) and only two TC joints of the normal persons had a value above it (4.1 and 5.4 mm). So, if the noechogenic space between the talus and the joint capsule was 3.1 mm or less, it was regarded as normal and if it was 3.2 mm or more, it was regarded as effusion. The clinical assessment and the US gave similar results in 35 TC joints, whereas they differed in the remaining 27 joints. The kappa coefficient between these investigations was 0.039 showing extremely poor agreement. Conclusion: These preliminary results indicate that clinical evaluation is not adequate in diagnosis of effusion and synovitis of TC joints in patients with RA. It is probable that the main source of error in this respect is tenosynovitis in the region of ankle. So, US may significantly mprove the accuracy of diagnosis of effusion and synovitis in these patients.